The effects of continuous nursing via the WeChat platform on neonates after enterostomy: a single-centre retrospective cohort study - Lijuan Wu; Ying Lin; Ruiyun Xue; Bin Guo; Jianxi Bai (BMC Nursing, 2023)
Abstract Background Temporary enterostomy is an effective treatment for various neonatal intestinal diseases. However, family caregivers find it challenging to provide the required nursing care. Nursing management is very important for reducing parents’ anxiety and improving the patients’ quality of life. This research aimed to compare the effects of continuous nursing using the WeChat platform with traditional nursing for neonates after enterostomy. Methods Neonates who underwent enterostomy from January 2014 to December 2020 in our hospital were retrospectively analysed. The patients were divided into the traditional nursing group and the continuous nursing group. The peri-stomal skin was evaluated with the DET scale. The mental status of the families was evaluated with the SAS and SDS. Results There were 143 patients in the traditional nursing group (TG) and 165 in the continuous nursing group (CG). The mean weight was 2.7 ± 0.6 kg in TG and 2.8 ± 0.5 kg in CG. The mean age at surgery was 4.9 ± 7.3 d in TG and 4.8 ± 7.55 d in the CG. No statistically significant differences between the two groups were found in the demographic information. The continuous nursing group had an obviously lower DET score for the peri-stomal skin than the traditional nursing group (P = 0.003). Three months after discharge from the hospital, the continuous nursing group replaced 7.2 ± 1.8 ostomy bags every week, significantly less than the traditional nursing group (P = 0.002). Three months after discharge, the continuous nursing group had better SAS and SDS scores than the traditional nursing group. Conclusions Continuous nursing based on WeChat can effectively improve the quality of life of neonates after enterostomy. Family members can also receive proper psychological counselling to relieve their anxiety and depression.